BODY BALANCE IN INDIVIDUALS WITH OSTEOARTHRITIS OF THE HIP AND KNEE, BEFORE AND AFTER GROUP PHYSIOTHERAPY INTERVENTION PROTOCOL - Leite, Alany Gabrielli [UNESP]; Watanabe, Gustavo Yuji [UNESP]; da Cruz Souza, Ariel Aparecido [UNESP]; Mantovani, Alessandra Madia; Fregonesi, Cristina Elena Prado Teles [UNESP] (Elsevier, 2024)
Background Osteoarthritis (OA) is a slow and progressive musculoskeletal disorder that primarily affects the hip and knee joints. As a result, it leads to loss of flexibility, pain, reduced range of motion, and affects gait and body balance, resulting in functional dependence and reduced quality of life for individuals. Physical therapy based on exercises is considered the best treatment option due to its favorable cost-benefit ratio, helping to reduce pain and improve physical function, gait, and body balance. Additionally, studies suggest that group physical therapy has proven beneficial as it utilizes fewer resources, thereby reducing costs, offering greater interaction among patients, and achieving similar results to individual treatment. Objectives This study aimed to evaluate the effects of a group exercise protocol on static and dynamic body balance in individuals with knee and hip osteoarthritis. Methods A clinical trial was conducted with patients diagnosed with knee and/or hip OA, who were able to walk independently and scored above 25 on the Lower Extremity Functional Scale (LEFS). The assessment instruments included the LEFS functionality questionnaire, Visual Analogue Scale (VAS) for pain assessment, Agility and Dynamic Balance Test (ÁGIL), and Stabilometry using an electronic baropodometer (FootWalk Pro®, AM CUBE, France), where participants maintained a bipedal position without support for 30 seconds. The intervention protocol consisted of 10 group kinesiotherapy sessions, conducted twice a week, with progressive exercises. The first week focused on mobility exercises involving active movements of the lower limbs, ballistic stretching, oscillations, and adopting different positions. The second week they emphasized mobility and resistance, incorporating shin pads and active lower limb exercises. In the third week, the focus was on resistance with higher intensity compared to the previous week. The fourth week they included resistance and functional exercises simulating musculoskeletal strain during daily activities. The fifth week involved functional exercises with increased intensity and additional balance training. Data were presented as means and standard deviations, and comparisons were made using dependent sample tests determined by the Kolmogorov-Smirnov test with the assistance of SPSS software (version 19.0) at a significance level of 5%. Results The sample comprised 27 participants, 20 women (74%) and seven men (26%), and a mean age of 64.19±8.33 years. After accounting for sample loss between the first and second evaluation moments (after intervention), there were 18 participants available for comparison tests. The results showed a significant 17% improvement in functional capacity and a 44% reduction in pain during movement. Conclusion The five-week group exercise protocol improved pain and functionality in this sample; however, it did not lead to significant changes in static and dynamic body balance parameters. Implications This study demonstrates the clinical applicability of group exercises, which can improve pain and function in patients with knee and/or hip osteoarthritis, thereby reducing costs and enhancing the efficiency of care in clinics.